The role of (dis)trust in disengagement and deradicalisation - Morrison, John; Silke, Andrew; Maiberg, Heidi; Slay, Chloe; Stewart, Rebecca (Centre for Research and Evidence on Security Threats, 2021)
When designing a disengagement or deradicalisation programme, who delivers it and how much they are trusted needs careful consideration. A systematic review of the disengagement and deradicalisation literature identified (dis)trust as playing a key filtering role in the disengagement and deradicalisation decision-making processes. It was found that the opportunities to leave a terrorist organisation are more likely to be successful when they are offered by an individual, organisation, or entity that is perceived by the would-be defector as being trustworthy. The same opportunity provided by a distrusted or less trusted entity is significantly less likely to lead to an organisational exit. Trust is most important at the initial stages of disengagement. However, if one is to have a sustained exit, these and other trusting relationships must be maintained.
CREST copyright requirements can be found at: https://crestresearch.ac.uk/about/copyright/
Keywords: Terrorism; Disengagement; Deradicalization